Majority religious politics: The struggle for religious rights of minorities in Sampang, Madura - Gilang Ramadhan (Universitas Trunojoyo Madura, 2022)
The strength of the discrimination against the Shiites in several places, especially in East Java, cannot be separated from the legitimacy given to the Tajul Muluk-led Shia heretical sect by the East Java MUI. One of the factors causing this discrimination is the difference in the perception of interests and the unequal quality of authority. In the case of Shia discrimination, certain positions in society delegate power and authority to other positions. This condition resulted in inequality in the status of Shiites as citizens’ rights and social subordination of the dominant group to other groups. This research was library research, where the researcher used data collection techniques with critical discourse analysis. In this study, the researcher interpreted the finding through literature, books, documents, and various digital and print reports related to Shia discrimination. In this study, the researcher found that the theological justification of the Sunni group is often used to discriminate against Shia. However, the basis of this problem is a conflict of political interest, where some groups are afraid of being dominated by others groups. Therefore, the researcher offered intrafaith dialogue to promote humanity by letting go of various political interests, as offered by Abu Nimer.